Effect of hypoxia on release TNF alpha by dendritic cells and macrophage derived from myeloid cells of mice (المجلة العلمية لكلية العلوم, 2025)
Hypoxia is low levels of oxygen and is a common feature during inflammation associated with numerous inflammatory diseases and infections. Dendritic cells and macrophages are significant immune defensive cells with a range of functions that include phagocytosis, secretion and release of an extensive kind of proteins including cytokines and chemokines, and are typically found in areas where oxygen availability is low, especially during inflammation. Tumor necrosis factor type alpha (TNF α) is a cytokine that is expressed by various cell types including macrophages, dendritic cells, and other non-immune cells against infections. It is an important pro-inflammatory cytokine that regulates inflammatory cells and responses.This study focused on comparing the effects of hypoxia on the release of TNF alpha levels by dendritic cells and macrophages derived from myeloid cells of C57BL/6J mice in vitro using the ELISA test. Hypoxia is used because of the associated changes in the living body of the mouse.Non-stimulated macrophages and dendritic cells derived from myeloid incubated in parallel in hypoxia and normoxia showed the production of TNF-α in both conditions; however, both dendritic cells and macrophages released more TNF-α in normoxia than in hypoxia. The production of TNF-alpha was higher in dendritic cells compared to macrophages. In brief, the comparisons between normoxia and hypoxia on the release of TNF alpha by dendritic cells and macrophages derived from myeloid cells of non-stimulated mice were shown.